O-031 Hyperacute cortical neuroplasticity following preoperative embolization of brain AVMs. (16th November 2010) - Eesa, M; Festa, J; Lazar, R; Meyers, P
Abstract : Purpose: Cerebral arteriovenous malformations (AVM) occur due to abnormal vascular morphogenesis, and reorganization of neurological function has been well documented in patients harboring them. Patients undergoing endovascular treatment for nidal reduction of brain AVMs prior to surgical resection may develop transitory neurological symptoms which may represent a manifestation of such a response occurring in a hyperacute fashion. The purpose of this study was to demonstrate any functional MRI (fMRI) evidence for hyperacute neuroplasticity in patients with brain AVMs undergoing pre-operative embolization. Materials and methods: 12 patients (aged 24–55 years; mean 38±7.6 years; nine men, 10 right-handed) with cerebral AVMs who underwent preoperative embolization at our center from 2004 to 2008 and elected to participate were included in the study. All patients had baseline MRI studies performed on 1.5 or 3 T GE Magnet which included blood oxygen level dependant (BOLD) fMRI studies using multiple motor, visual and language paradigm(s). Patients were pretreated with anticonvulsants and maintained therapeutic levels. Patients then underwent diagnostic catheter angiograms, superselective arteriography and provocative testing (WADA) prior to the embolization in the same procedure. Patients were then taken for repeat fMRI studies within 1–2 h. Pre and post-embolization fMRI data were evaluated by readers who were blinded to the patient data. The BOLD fMRI data was coregistered onto the structural images and categorized as no reorganization or definite reorganization of neurological function. Results: A total of 12 eloquent region AVMs were treated in 12 patients. There were two grade II and 10 grade III AVMs. All patients underwent an embolization procedure as per the institutional protocol with the aim of nidal penetration and maximal nidal reduction using n-butyl cyanoacrylate (Trufil NBCA: Cordis Neurovascular, Raynam, Massachusetts, USA). There were no major (stroke or death) or minor complications. One patient developed a transient neurological deficit (aphasia) immediately following endovascular treatment and was shown to have relocated language function without diffusion weighted infarction. There were no hemorrhagic complications. Conclusions: Hyperacute neuroplasticity may be demonstrated in patients with cerebral AVMs undergoing preoperative embolization and occlusion. This may explain some of the transient neurological deficits that are not uncommonly seen in such patients. Improved characterization of this neuroplastic response may be useful in the treatment planning of AVM patients and rehabilitative care of acute stroke patients.